Technology Negotiation in Dangdut Koplo’s Ecosystem and Practices - Michael H. B. Raditya (Universitas Gadjah Mada, 2022)
This article deals with the negotiation between the subgenre of Dangdut and technology. In this article, I articulate how agents of Dangdut Koplo use digital technology and how digital technology affects Dangdut Koplo’s ecosystem, cultural, and social practices. It is necessary to discuss Dangdut Koplo because it has several practices that are impacted by technology. Their practices elaborate on how society negotiated the use of technology. Dangdut koplo is one of the regional dangdut (dangdut daerah) subgenres that has developed in Indonesia, particularly East Java. Dangdut koplo emerged in the 1990s in Jarak Street, Surabaya, East Java. Furthermore, I will refer to two moments that demonstrated the impact of technology on the subgenre: first, the local people's activation of the local recording industry, and second, the activation of the internet and digital platforms by local people. I will elaborate on these to show the negotiation pattern between technology and their music, Dangdut Koplo. At the first moment, technological advances made people develop their local industries. The existence of local industries changed their economic and cultural patterns. Furthermore, middlemen in the music industry that Jakarta previously monopolized shifted to their surroundings. As a result, they could activate and directly control their economy and society. Then, the first moment developed rapidly in the second moment, when the internet changed society's social, economic, and cultural patterns. The internet allowed everyone to distribute their work. They could directly access consumers without the role of the previous middleman. Melayu Orchestra does not need a local music label or distributor with a solid fan base. They could distribute their works on the internet and digital platforms. This technological impact meant the Melayu Orchestra could compete with the local recording industry and vice versa. This pattern also changed their production processes, where digital needs made daily impressions, the development of Melayu orchestra personas on gadget screens, etc. Based on these developments, I elaborated on these questions: How did the ecosystem changes and its relationships impact the dangdut community? How is the dangdut community negotiating with technology? Utilizing digital data and observation data (obtained in 2017), I articulate how technological developments changed society's ecosystem and practice; and how society deals with technology.